A man of much importance the art and life of Terrence McNally - Byrne, Christopher (Applause Theatre & Cinema Books, 2023)
"An in-depth, intimate look at the life of playwright Terrence McNally over his nearly sixty-year career and the development of an artist reflecting a dynamic world, onstage and off"--